The Effect of Green Investment and Board Diversity on Carbon Emission Disclosure in Energy Sector Companies in Indonesia - Ghaniya Ariska Fidiano; Ayu Aryista Dewi (E-Jurnal Akuntansi, 2026)
Carbon emission disclosure reflects a company's environmental commitment. This research aims to assess the role of green investment, board gender diversity, and board educational background affect carbon emission disclosure in energy sector companies in Indonesia during the 2021–2024 period. Total of 112 observations were selected using purposive sampling and examined using multiple linear regression. The findings show that green investment and the proportion of board members with economics and business education enhance carbon emission disclosure. In contrast, the proportion of female directors shows no significant effect. These findings contribute to the development of stakeholder and legitimacy theories and offer implications for companies, investors, and policymakers.